ANALISIS KESEDIAAN MEMBAYAR UNTUK RUMAH KELOMPOK MASYARAKAT BERPENDAPATAN RENDAH DI KOTA BANDA ACEH - Cut Zakia Rizki; Muhammad Ilhamsyah Siregar (Syiah Kuala University, 2018)
AbstractThis study aims to analyze the effect of various economic variables (ie education level and number of family members), hedonic variables (current occupied homes, number of bedrooms, number of living rooms, and bathrooms), spatial variables (range of house to market, workplaces and medical facilities) as well as amenitative variable (ie water network availability, garbage collection services availabilty, flood-free areas, and healthy environment) to the willingness to pay for homes for low-income groups in Banda Aceh City. The result of this study concluded that economic variables and some hedonic variables affect the willingness to pay for homes in poor communities in Banda Aceh city, while spatial and amenitative variables do not affect significantly. The total desire to pay is almost Rp.210 million or an average of Rp.1 million per month. Therefore, the government should provide a relatively cheaper vertical model housing for land acquisition, and easier provision of basic housing infrastructure.